The Effect of Combined Plyometric and Resistance Training on Lower Limb Explosive Power in Adolescent Volleyball Athletes - Yoel Hardi Saputra Gultom; Muhammad Hasan Shiddiq; Attila Bahri; Mhd Bisma Hadi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the effects of plyometric training, resistance training, and their combination on improving lower-limb explosive power in adolescent volleyball athletes. Explosive power plays a crucial role in volleyball performance, particularly in executing movements such as spike, block, and jump serve. A quasi-experimental design with a pretest, posttest model was employed involving three intervention groups, each consisting of 20 adolescent athletes. The interventions included plyometric training, resistance training, and a combination of both over a six-week period. Vertical Jump Test was used to measure lower-limb explosive power before and after the intervention. The results showed significant improvements in all groups (p < 0.001), indicating that each training model effectively enhanced explosive power. The combination group demonstrated the highest improvement (Δ = 7.35 cm), followed by the plyometric group (Δ = 5.10 cm) and the resistance training group (Δ = 4.44 cm). One-way ANOVA revealed significant differences in improvement among the groups (p < 0.001), with post hoc Tukey analysis confirming that the combination group outperformed the other two. The effect size (η² = 0.517) indicated a strong influence of training type on performance enhancement. In conclusion, although all training methods effectively improved lower-limb explosive power, the combination of plyometric and resistance training produced the most substantial effect. This combined training method is recommended for coaches and practitioners seeking to optimize explosive performance in adolescent volleyball athletes.